Smoke Gets in Their Eyes? Third-Person Effects of Electronic Cigarette Advertising. (3rd September 2017) - Pardun, Carol J.; McKeever, Robert; Bedingfield, Sid
ABSTRACT: This study examined the relationship between smoker status and attitudes toward e-cigarette usage, third-person perceptions of e-cigarette advertising, and support for regulation of e-cigarette advertising within the context of a media-saturated environment. Survey results ( n = 615) indicated that participants perceived e-cigarette advertisements as having a more powerful effect on others than on themselves and that nonsmokers perceived this more strongly than did smokers. Nonsmokers were found to have more negative attitudes toward e-cigarette use than smokers. Mediation analysis indicated support for a serial indirect effect of smoker status on support for regulation through attitudes toward e-cigarettes and third-person perceptions.